A DISTRIBUTION SYSTEM DESIGN MODEL: A DISTRIBUTION SYSTEM DESIGN MODEL - Bogdanov, Andrey (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Large varieties of mathematical programming models have been developed to provide decision support to the design engineer. The paper deals with some of the problems and offers practical solutions.